A Study of Image Processing in Agriculture Application under High Performance Computing Environment - Abdul Rahman, Mohd Nordin; A Nasir, A Fakhri; Mamat, Rasid (2012)
The available literatures on image processing in agriculture application under high performance computing (HPC) are limited and sometimes are not discussed in details. This paper reviewed the steps of image analysis done in some image processing focusing on agriculture application and also the details analysis of parallel and distributed image processing. The memory architecture in parallel and distributed image processing and some suitable application programming interface (API) in parallel and distributed image processing are examined. In general, this study provides basic understanding of parallel and distributed image processing for agriculture application.